Computational collective intelligence. 9th International Conference, ICCCI 2017, Nicosia, Cyprus, September 27-29, 2017, Proceedings /: 9th International Conference, ICCCI 2017, Nicosia, Cyprus, September 27-29, 2017, Proceedings. Part II : (2017) - Unknown
No abstract available